1993
DOI: 10.1088/0031-8949/48/2/022
|View full text |Cite
|
Sign up to set email alerts
|

Nucleon-nucleon potentials from inversion

Abstract: Quantum inversion theory has been applied to theSchrodinger operator and is used to obtain NN potentials to partial wave phase shifts. We solved the Gelfand-Levitan and Marchenko fundamental inversion equations and determined from the output-kernels the energy independent and local r-space potentials. The results are based on phase shift data from experimental and theoretical sources where a point charge Coulomb reference potential was added for pp data. Potentials are given for the single channel ' S o , ' P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Our potential selection coxnprises inversion potentials based on phase-shift analyses by Amdt-FA91 [23] and Nijmegen-II [6,10] and phase shifts from the Bonn-B potential [4]. The Nijmegen phases have a y2 1, the lowest claimed so far in a phase-shift analysis.…”
Section: Bremsstrahlung Potential Model and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our potential selection coxnprises inversion potentials based on phase-shift analyses by Amdt-FA91 [23] and Nijmegen-II [6,10] and phase shifts from the Bonn-B potential [4]. The Nijmegen phases have a y2 1, the lowest claimed so far in a phase-shift analysis.…”
Section: Bremsstrahlung Potential Model and Resultsmentioning
confidence: 99%
“…Discrepancies of these potentials in breakup Faddeev calculations and few-body and nuclear-matter binding energies systematically show that something is missing in these potentials [12 -14]. It is generally agreed upon that local potentials always underbind triton by 800 + 150 keV [10,12] whereas Bonn-B misses the experimental binding energy of 8.45 MeV only by 250 keV [4]. This is a significant result in favor of a significant nonlocality in nucleon-nucleon potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we omit the second term in (7) since it becomes negligible at large distances with respect to the first term. Thus, solution u(k, r) may be obtained as…”
Section: Two Channel Scattering With Equal Thresholdsmentioning
confidence: 99%
“…quite difficult to generalize. Using the Marchenko equation, the results of Newton and Fulton were nevertheless reproduced and improved by von Geramb et al [7]. A review of the present state of the art in the inverse scattering methods may be found in [8]- [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, for reasons of fairness, we like to stress that our sub-selection is essentially accidental, and that there are many other, equally representative examples for each stage of the development of theoretical nuclear potentials. In particular, we mention the potential by Tourreil, Rouben, and Sprung [7], the Argonne V 14 potential [8], and the more recent models developed at Bochum [9], Williamsburg [10], and Hamburg [11].…”
Section: Introductionmentioning
confidence: 99%